The Personalization of Politics in Anglo-American Democracies - Bittner, Amanda (Frontiers in Political Science, 2021)
In American politics, few argue with the idea that leaders matter: the media closely tracks the performance and activities of Joe Biden and Donald Trump, for example, suggesting to us that who they are matters. Voters indicate on their ballot which presidential candidate they prefer, marking an x next to the person’s name, giving further credence to the idea that the individual matters in the process. Contemporary Anglo-Westminster-style democracies have many things in common with the United States, but operate with completely different political systems, and without a direct vote for a specific party leader. What is the relationship between voters and party leaders in these contexts? Do party leaders matter the same way in these countries? Has this relationship changed over time? Are we really seeing the personalization of parliamentary elections, as some scholars have suggested? The personalization literature provides us with mixed evidence of the increasing importance of leaders, and part of the reason for that maybe linked to the lack of comparable data. This paper assesses the role of leaders in the US as well as four parliamentary democracies (Britain, Canada, New Zealand, and Australia) over time. Combining data from the election studies of these five countries from the 1960s to the present, the analyses presented here suggest that leaders are not increasingly important to voters over time, but that leaders have always been important to election outcomes. What has changed over time, however, is the way partisans see the leaders of other parties. Partisans are increasingly polarized in their views of opposing party leaders, and this has the potential to change the impact of leaders in the electoral process.